Beauty in everyday motion: Electrophysiological correlates of aesthetic preference for human walking - Hayashi, Sayuri; Nishimura, Yuki; Ikeda, Yuki; Nakashima, Hiroki; Egashira, Yuka; Ukezono, Masatoshi; Uono, Shota; Okada, Takashi; Higuchi, Shigekazu (Neuropsychologia, 2022)
Aesthetic preference occurs in everyday experience. Studies have suggested that aesthetic preference (such as observing other's motion) affects social interaction via enhanced neural processing. This study investigated the effect of aesthetic preference on neural activities, in response to walking motion. Twenty participants observed biological motion (BM) representing three walking types (model-posture, good-posture, and bad-posture) and their scrambled motion (SM) during the event-related potentials measurement. The N200 and N300 amplitudes, reflecting the early sensory and the later integrational processes, were analyzed. The results revealed that the N200 amplitude of BM was greater than that of SM in the good- and bad-posture conditions. The N300 amplitude was larger in BM than SM regardless of the walking type. Exploratory regression analyses indicated that the N300 for BM, but not for SM or N200, was more negatively deflected with the increase of aesthetic preference scores. Our findings suggest that aesthetic preference enhances the later integrational process of BM represented in the N300 amplitude, whereas the early perceptual process (reflected by the N200 amplitude) is potentially modulated by familiarity rather than aesthetic preference in other's motion. •Neuroaesthetic effects on recognition of a walk were investigated.•The N200 of BM was greater than that of SM in the good- and bad-posture conditions.•The N300 was larger in BM than SM regardless of walking types.•Large N300 were correlated with strong aesthetic preference for BM.